Sesquiterpene Lactones from Cynara cornigera: Acetyl Cholinesterase Inhibition and In Silico Ligand Docking - Hegazy, Mohamed-Elamir F.; Ibrahim, Abeer Y.; Mohamed, Tarik A.; Shahat, Abdelaaty A.; El Halawany, Ali M.; Abdel-Azim, Nahla S.; Alsaid, Mansour S.; Paré, Paul W. (Planta Medica, 2016)
Wild artichoke (Cynara cornigera), a thistle-like perennial belonging to the Asteraceae family, is native to the Mediterranean region, northwestern Africa, and the Canary Islands. While the pleasant, albeit bitter, taste of the leaves and flowers is attributed to the sesquiterpene lactones cynaropicrin and cynarin, a comprehensive phytochemical investigation still needs to be reported. In this study seven sesquiterpene lactones were isolated from an aqueous methanol plant extract, including a new halogenated metabolite (1), the naturally isolated compound sibthorpine (2), and five metabolites isolated for the first time from C. cornigera. Structures were established by spectroscopic methods, including HREIMS, 1 H, 13 C, DEPT, 1 H-1 H COSY, HMQC, and HMBC-NMR experiments as well as by X-ray analysis. The isolated bioactive nutrients were analyzed for their antioxidant and metal chelating activity. Compound 1 exhibited a potent metal chelating activity as well as a high antioxidant capacity. Moreover, select compounds were effective as acetyl cholinesterase inhibitors presenting the possibility for such compounds to be examined for anti-neurodegenerative activity. A computational pharmacophore elucidation and docking study was performed to estimate the pharmacophoric features and binding conformation of isolated compounds in the acetyl cholinesterase active site.
Keywords: Cynara cornigera; Asteraceae; sesquiterpene lactones; acetyl cholinesterase inhibition; in silico ligand docking